GABAergic synaptic transmission and cortical oscillation patterns in the primary somatosensory area of a valproic acid rat model of autism spectrum disorder. (27th December 2022) - Fontes‐Dutra, Mellanie; Righes Marafiga, Joseane; Santos‐Terra, Júlio; Deckmann, Iohanna; Brum Schwingel, Gustavo; Rabelo, Bruna; Kazmierzak de Moraes, Rafael; Rockenbach, Marília; Vendramin Pasquetti, Mayara; Gottfried, Carmem; Calcagnotto, Maria Elisa
Abstract: Autism spectrum disorder (ASD) is characterized by impaired social communication and interaction associated with repetitive or stereotyped behaviour. Prenatal valproic acid (VPA) exposure in rodents is a commonly used model of ASD. Resveratrol (RSV) has been shown to prevent interneuronal and behavioural impairments in the VPA model. We investigated the effects of prenatal VPA exposure and RSV on the GABAergic synaptic transmission, brain oscillations and on the genic expression of interneuron‐associated transcription factor LHX6 in the primary somatosensory area (PSSA). Prenatal VPA exposure decreased the sIPSC and mIPSC frequencies and the sIPSC decay kinetics onto layers 4/5 pyramidal cells of PSSA. About 40% of VPA animals exhibited absence‐like spike–wave discharge (SWD) events associated with behaviour arrest and increased power spectrum density of delta, beta and gamma cortical oscillations. VPA animals had reduced LHX6 expression in PSSA, but VPA animals treated with RSV had no changes on synaptic inhibition or LHX6 expression in the PSSA. SWD events associated with behaviour arrest and the abnormal increment of cortical oscillations were also absent in VPA animals treated with RSV. These findings provide new venues to investigate the role of both RSV and VPA in the pathophysiology of ASD and highlight the VPA animal model as an interesting tool to investigate pathways related to the aetiology and possible future therapies to this neuropsychiatric disorder. Abstract : The animal model of autism is induced by prenatal exposure to valproic acid (VPA) in gestational day E12.5. Prenatal treatment with resveratrol (RSV) was able to prevent both altered cortical oscillations and reduced sIPSC at layer 4/5 in primary somatosensory area induced by VPA administration. Molecular alterations in transcription factor LHX6 induced by VPA were prevented by prenatal treatment with RSV.